Challenges of Elementary Education: Curriculum Incompatibility Towards Students Learning Motivation at Bangbayang Elementary School - Khoerunnisa, Rahmania; Dewitri Yulianti; Rifky Aditya Ramadhan (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to examine the challenges faced in implementing the curriculum at the elementary school level, particularly regarding the incompatibility of the curriculum with the learning motivation of students at SDN Bangbayang. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that most of the material in the curriculum has not been fully adapted to the local context, interests, and learning needs of students. This has an impact on the lack of learning motivation, active participation, and student involvement in the learning process. In addition, limited resources and teacher training in implementing the curriculum flexibly are also inhibiting factors. This study recommends the need to adjust the curriculum based on student needs and teacher training so that learning is more contextual and motivating. Thus, it is hoped that a more relevant curriculum can improve the quality of education and encourage students to be more active in learning. This adjustment is also important to create a learning environment that is more inclusive and responsive to student needs.